Calcium signaling at the endoplasmic reticulum: fine-tuning stress responses. (March 2018) - Carreras-Sureda, Amado; Pihán, Philippe; Hetz, Claudio
Graphical abstract: Abstract: Endoplasmic reticulum (ER) calcium signaling is implicated in a myriad of coordinated cellular processes. The ER calcium content is tightly regulated as it allows a favorable environment for protein folding, in addition to operate as a major reservoir for fast and specific release of calcium. Altered ER homeostasis impacts protein folding, activating the unfolded protein response (UPR) as a rescue mechanism to restore proteostasis. ER calcium release impacts mitochondrial metabolism and also fine-tunes the threshold to undergo apoptosis under chronic stress. The global coordination between UPR signaling and energetic demands takes place at mitochondrial associated membranes (MAMs), specialized subdomains mediating interorganelle communication. Here we discuss current models explaining the functional relationship between ER homeostasis and various cellular responses to coordinate proteostasis and metabolic maintenance.